Financial and economic assessment of tidal stream energy: A case study - Stocker Klaus (International Journal of Financial Studies, 2020)
This case study is based on actual project and consultancy work, balancing real life experience with a review and analysis of empirical and theoretical literature. Tidal stream energy (TSE) is still a nascent technology, but with much better predictability than the classical alternatives of sun and wind. Being still more expensive than other renewable technologies, it is important to find locations in order to initiate a learning process to bring down cost to a competitive level as it was the case for solar and wind technologies. Locations for an initial phase of operation of TSE small islands in the Philippines (and other Asian countries) were found to be most suitable, because expensive and polluting diesel generators can be replaced and a reliable 24 h electricity supply can be established. Different appraisal methods in different scenarios show that under normal circumstances a hybrid combination of TSE, solar energy and battery storage is financially and economically superior to existing fossil energy based power stations as well as to solar energy alone. However, the traditional financial approaches are not always reliable, in spite of superficial mathematical exactness, and the parameters used must be analysed carefully, especially if we deal with innovative technologies with fast changes. In times of global warming we must also include the controversial issue of evaluating damages from greenhouse gases if choosing fossil alternatives. When evaluating and planning renewable technologies, engineering know-how is important, but insufficient. Since financing is a crucial issue for most renewable technologies with high front loaded cost and long amortisation periods, a thorough and trustworthy financial and economic analysis is necessary not only to avoid financial failure later on, but also to attract stakeholders like private investors, banks and government institutions to support a still unknown technology.
Keywords: M02; 330; renewable energy; tidal stream; photovoltaics; wind energy; hybrid system; financing; discount rate; social discount rate; greenhouse gas; CO2-price; ocean energy; PV; learning effects